2020
DOI: 10.3390/nu12113568
|View full text |Cite
|
Sign up to set email alerts
|

In Love with Shaping You—Influential Factors on the Breast Milk Content of Human Milk Oligosaccharides and Their Decisive Roles for Neonatal Development

Abstract: Human milk oligosaccharides (HMOs) are structurally versatile sugar molecules constituting the third major group of soluble components in human breast milk. Based on the disaccharide lactose, the mammary glands of future and lactating mothers produce a few hundreds of different HMOs implicating that their overall anabolism utilizes rather high amounts of energy. At first sight, it therefore seems contradictory that these sugars are indigestible for infants raising the question of why such an energy-intensive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 279 publications
(411 reference statements)
2
17
0
Order By: Relevance
“…However, among these, the genus Bifidobacterium soon becomes dominant. In fact, it can represent up to 90% of the microbiota of a breastfed baby while, in many formula-fed infants, they have been found in more modest quantities (about 50%), very similar to the concentrations of Bacteroides [ 45 ].…”
Section: Human Milk Oligosaccharides: Biological Functions Behind Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, among these, the genus Bifidobacterium soon becomes dominant. In fact, it can represent up to 90% of the microbiota of a breastfed baby while, in many formula-fed infants, they have been found in more modest quantities (about 50%), very similar to the concentrations of Bacteroides [ 45 ].…”
Section: Human Milk Oligosaccharides: Biological Functions Behind Physiologymentioning
confidence: 99%
“…This feature seems to be the result of an intense and selective evolutionary pressure of millions of years in order to better meet the survival needs of children [ 46 ]. However, this property is not exclusive to the Bifidobacterium genus but also belongs to some species of Bacteroides , Enterococcus , Lactobacillus , Streptococcus and Clostridium cluster IV/XIVa [ 45 ]. In fact, Borewicz et al [ 47 ] showed that the degree of metabolization of oligosaccharides is closely related to the presence of the genera Bifidobacterium , Bacteroides and Lactobacillus .…”
Section: Human Milk Oligosaccharides: Biological Functions Behind Physiologymentioning
confidence: 99%
“…Human milk, aside from its value as a source of food for the new-born infant, has increasingly been shown to have many additional benefits in promoting development and providing protection from diseases. Human milk oligosaccharides (HMOs) are the third most abundant constituent of milk, after lactose, and lipids, with total mean concentrations ranging from 4–30 g/L 1 . The majority of these complex oligosaccharides are based on free lactose.…”
Section: Introductionmentioning
confidence: 99%
“…Human milk, aside from its value as an optimal source of food for the new-born infant, has increasingly been shown to have many additional benefits in promoting development and providing protection from disease. Human milk oligosaccharides (HMOs) are the third most abundant constituent of milk, after lactose, and lipids, with total mean concentrations ranging from 4-30 g/L [1]. The majority of these complex oligosaccharides are typically based on free lactose.…”
Section: Introductionmentioning
confidence: 99%